2016
DOI: 10.1002/cne.24001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multiciliated ependymal cells that emerge in the neurogenic niche of the aged zebrafish brain

Abstract: In mammals, ventricular walls of the developing brain maintain a neurogenic niche, in which radial glial cells act as neural stem cells (NSCs) and generate new neurons in the embryo. In the adult brain, the neurogenic niche is maintained in the ventricular-subventricular zone (V-SVZ) of the lateral wall of lateral ventricles and the hippocampal dentate gyrus. In the neonatal V-SVZ, radial glial cells transform into astrocytic postnatal NSCs and multiciliated ependymal cells. On the other hand, in zebrafish, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
1
25
0
2
Order By: Relevance
“…From fish to mammals, the brain ventricles of vertebrates are decorated with motile ciliated cells [ 12 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 ]. It is, however, less clear when these motile ciliated cells appear during development and whether they occupy specific spatial locations, which could facilitate their function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From fish to mammals, the brain ventricles of vertebrates are decorated with motile ciliated cells [ 12 , 14 , 15 , 16 , 17 , 24 , 25 , 26 , 27 ]. It is, however, less clear when these motile ciliated cells appear during development and whether they occupy specific spatial locations, which could facilitate their function.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, motile ciliated cells in the larval zebrafish brain ventricles appear to be monociliated and beat in a rotational movement, which is typical for monociliated cells, including sperm [ 41 ] and cells in the left-right organizer [ 42 ]. Few studies reported multiciliated ependymal cells in the adult zebrafish, in the ventricle wall located between the corpus cerebelli and the medulla oblongata [ 17 ] and in the diencephalic and telencephalic ventricle [ 25 , 26 ], where foxj1a is expressed [ 56 ]. It will be exciting to investigate whether these multiciliated cells and the monociliated cells we identified at larval stage arise from the same progenitor pool and co-exist in the adult zebrafish brain.…”
Section: Discussionmentioning
confidence: 99%
“…The multiciliated cells that we identified in the cervical spinal cord of froglets do not seem to have counterparts in other nonmammalian species. For example, in zebrafish, multiciliated cells have only been described in the brain ventricles (Ogino et al ). Interestingly, in mammals multiciliated cells without proliferative capacity are present in macaque and human spinal cord (Alfaro‐Cervello et al, ), but not in rodents (Alfaro‐Cervello et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Already in 1836, the neuroanatomist Purkinje described ciliary beating on cells along the sheep ventricles [127]. Since then, these cells, referred to as ependymal cells (ECs), have been described in both fish [32,110,[128][129][130], amphibians [131][132][133] and mammals [16,123]. Traditionally, the ECs of the brain are defined as Foxj1positive, motile ciliated, cuboidal cells generating nearwall CSF flow [16,32,[133][134][135][136].…”
Section: Development and Cellular Composition Of The Brain Ventriculamentioning
confidence: 99%